Accidental hypothermia and prolonged fasting in the immediate preoperative: analysis in a university hospital (Research, Society and Development, 2022)
Objectives: to identify the relationship between unintentional hypothermia and prolonged fasting in a group of surgical patients in the immediate preoperative period; to evaluate the mean value of axillary temperature, and the mean fasting time of patients in the immediate preoperative period. Method: a cross-sectional study with a quantitative approach, carried out in inpatient units of a university hospital located in the city of Rio de Janeiro. 30 medical records of patients in the immediate preoperative period of general surgery were used. Data collection was carried out in September, through a questionnaire. Data were organized in Excel spreadsheets and analyzed using simple descriptive statistics. Results: the sample consisted of 11 men and 19 women, aged between 22 and 92 years. The prevalent surgical procedures were hernioplasty (36.70%) and thyroidectomy (16.66%). Of the total number of patients, 17 (56.67%) were referred to the operating room with a maximum temperature of 36oC. Concomitance between hypothermia and prolonged fasting time was evidenced. The mean temperature value of the patients at the time of referral to the operating room was 35.9°C and the mean fasting time was 12.47 hours. Conclusion: the results demonstrate the need for greater attention to national and international recommendations on fasting time for patients in the immediate preoperative period.